Tailspin ebook - Brown, Sandra (2018)
From a New York Times bestselling author, a daring pilot races against time to deliver an important package–and keep it from falling into the wrong hands. Rye Mallett is a fearless pilot with a reputation and a deadline to uphold. When he's asked to deliver a mysterious black box to Dr. Lambert, he doesn't ask questions. After a sabotage attempt on his plane, he's greeted by the mysterious Dr. Brynn O'Neal. Rye finds himself irresistibly drawn by the intrigue surrounding his cargo...and the alluring Brynn. Soon, Rye and Brynn are in a treacherous forty-eight-hour race to deliver the box. With everyone from law enforcement to hired guns hot on their heels, they must learn to trust each other to protect their valuable cargo–and their lives–from those who would kill for it.